1970
DOI: 10.32413/pjph.v7i2.41
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Choosing Specialty After Graduation Among Students of a Private Medical College in Pakistan

Abstract: Background: Diverse factors influence the career choice of undergraduate medical students. This study was carried out to identify career preferences and factors influencing their selection among undergraduate medical students Methods: The descriptive cross sectional study was conducted among under graduate students. Final MBBS medical students (84) were interviewed. They were interviewed for career preference after finishing medical school and then for reasons of choosing a specific specialty. All information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To demonstrate the overall expertise and experience in otorhinolaryngology, various questions were asked and evaluated and were put along to enhance the preferences of individuals regarding the otorhinolaryngology as the field of specialty. A Likert scale was selected having numbering from 1-5 in which, strongly agree [1], agree [2], not sure [3], disagree [4], strongly disagree [5]. The document was prepared in accordance with the "uniform requirements submitted to biomedical journals" 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the overall expertise and experience in otorhinolaryngology, various questions were asked and evaluated and were put along to enhance the preferences of individuals regarding the otorhinolaryngology as the field of specialty. A Likert scale was selected having numbering from 1-5 in which, strongly agree [1], agree [2], not sure [3], disagree [4], strongly disagree [5]. The document was prepared in accordance with the "uniform requirements submitted to biomedical journals" 15 .…”
Section: Methodsmentioning
confidence: 99%
“…The field demands to visit patients in the off time and having night duties as well owing to the critical condition of the patients 3,4 . In this regard, the field of otorhinolaryngology provides with more regulated life style 5 and it is the most valuable specialty in United States 6 . A suitable training of this specialty is also necessity for good general practitioners as around 40-60% of patients are being visited routinely with ear, nose and throat diseases in their outpatient clinics 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted to attribute uncertainty to factors such as burnout and increased levels of stress in the medical field (7). One study even reported that students preferred clinical sciences over basic sciences (8). The wide variety of factors reported across different studies shows that a lot goes into selecting a specialty.…”
Section: Introductionmentioning
confidence: 99%